2014
DOI: 10.5114/wiitm.2014.41631
|View full text |Cite
|
Sign up to set email alerts
|

Single incision approach to totally extraperitoneal inguinal hernia repair.

Abstract: IntroductionNowadays the vast majority of inguinal hernia repairs are laparoscopically assisted. Single incision laparoscopy aims to accelerate recovery and provide a better cosmetic outcome after the operation.AimTo present our own modification of the totally extraperitoneal (TEP) procedure with a single incision and without a multiport, and compare the results with those obtained in the classic three-trocar TEP method.Material and methodsThe study group comprised 61 males. The first group consisted of 35 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…It gives trainees the opportunity to see many experienced surgeons at work and to learn from them. This allows them to obtain knowledge about various surgical techniques and gain the ability to think multidimensionally [ 17 20 ]. Smietanski, in his article “The influence of carrying out multicentre trials on surgical practice in general surgery departments”, showed that only exchange of knowledge and internships in different units, from district to university hospitals, can improve the training of young surgeons [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It gives trainees the opportunity to see many experienced surgeons at work and to learn from them. This allows them to obtain knowledge about various surgical techniques and gain the ability to think multidimensionally [ 17 20 ]. Smietanski, in his article “The influence of carrying out multicentre trials on surgical practice in general surgery departments”, showed that only exchange of knowledge and internships in different units, from district to university hospitals, can improve the training of young surgeons [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic technique has gained in popularity because it combines the advantages of minimally invasive technique and mesh usage [ 29 ]. The main advantages of this technique is minimization of postoperative pain, shortening the period of convalescence, reducing the wound complications and others connected with laparotomy [ 30 , 31 ]. In parastomal hernia surgery laparoscopy allows for minimization of the postoperative wound and complications associated with it.…”
Section: Discussionmentioning
confidence: 99%
“…The 2014 study by Lai et al incorporated eight clinical trials—two on percutaneous extraperitoneal closure (PEC) , one on TAPP , and five on TEP —in its quantitative analysis; the eight trials had a total of 926 patients . A study by Luo et al published in 2017 included 17 clinical trials—2 on PEC , 2 on TAPP , and 13 on TEP —in its quantitative analysis; the 17 trials had a total of 1737 patients . The 2016 study by Sajid et al incorporated 15 trials—2 on PEC , 1 on TAPP , 11 on TEP , and 1 with combined results from TAPP and TEP —in its quantitative analysis; the 15 trials had a total of 1651 patients .…”
Section: Current Evidencementioning
confidence: 99%
“…The 2014 study by Siddiqui et al included three studies that analyzed a total of 287 patients (LESS, 128; conventional, 159) . The 2016 study by Lo et al included seven additional studies, for a total of 10, in its quantitative analysis ; these studies included four RCT, three prospective studies, and three retrospective studies, with a total of 1109 patients (LESS TEP, 595; conventional TEP, 514). The study by Lo et al found unilateral LESS TEP took significantly longer than conventional TEP ( P = 0.02); there was no significant heterogeneity of data from the studies used.…”
Section: Current Evidencementioning
confidence: 99%